Comparing the use of risk-influencing production inputs and experimentally measured risk attitude: Do decisions of Indonesian small-scale rubber farmers match? - Stefan Moser; Oliver Mußhoff (GOEDOC, Dokumenten- und Publikationsserver der Georg-August-Universität, 2015)
This article compares the use of risk-increasing and risk-reducing production inputs with the experimentally measured risk attitudes of farmers. For this purpose, the Just-Pope production function indicates production inputs' influence on output risk and a Holt-Laury lottery is used to measure the producers risk attitude. We test whether more risk averse farmers use more risk-reducing and less risk-increasing production inputs. Therefore, we apply a unique data set which includes 185 small-scale farmers which are producing rubber on 260 plots on the island of Sumatra, Indonesia. The Just-Pope production function indicates that fertiliser usage has a risk-reducing effect, whereas herbicide usage and plot size have risk-increasing effects. For labour and plantation age, the influence on output risk is ambiguous. By including the outcome of a Holt-Laury lottery into the analysis, we found the expected result that more risk averse farmers use more (risk-reducing) fertiliser and less (risk-increasing) herbicides. These consistent results provide an example for the external validity of measuring risk attitude with the Holt-Laury lottery.
urn:nbn:de:gbv:7-webdoc-3957-8
Keywords: C91; C93; Q12; 330; Holt-Laury lottery; Just-Pope production function; output risk; rubber; Indonesia